KEPADATAN DAN SEBARAN TERITIP (Amphibalanus spp.) DI PELABUHAN KOTA DUMAI - Muhammad Arif Nasution; Al Mudzni (Universitas Teuku Umar, 2016)
Barnacle (Amphibalanus spp.) density and distribution implemented in September-November 2013 in the port of Dumai, Riau, which aims to explore the causes of inequality in the spatial distribution of density Barnacles (Amphibalanus spp). in different media attachment were influenced by marine environmental conditions in the port of Dumai. Barnacle density observation method in this study is the stratified random sampling method using wood, fiber and iron as a media attachment. The results showed the existence of inequality Barnacle density (Amphibalanus spp). on the media attachment with different types and colors. The highest average Barnacle density was found in colorless timber, which ranges between 265-506 ind/m2. While the lowest average Barnacle density was found in white fiber and it ranged between 25-68 ind/m2.